Dear Papa, dear Hotch the correspondence of Ernest Hemingway and A. E. Hotchner - Hemingway, Ernest 1899-1961; Hotchner, A. E. (Univ. of Missouri Press, 2005)
"The collected correspondence between Ernest Hemingway and A.E. Hotchner. Includes more than 160 letters, cables, and cards the two friends exchanged from 1948 to 1961. With annotations and a textual commentary that enables readers to reconstruct the features of the original manuscripts and envelopes"--Provided by publisher.
"The collected correspondence between Ernest Hemingway and A. E. Hotchner. Includes more than 160 letters, cables, and cards the two friends exchanged from 1948 to 1961. With annotations and a textual commentary that enables readers to reconstruct the features of the original manuscripts and envelopes"--Provided by publisher.
Includes bibliographical references and index
Keywords: Hemingway, Ernest <1899-1961> - Correspondance; Hotchner, A. E - Correspondanc; Hemingway, Ernest -- 1899-1961 -- Correspondence; Hotchner, A. E -- Correspondence; Hemingway, Ernest -- 1899-1961; Hotchner, A. E. -- 1917-2020; Geschichte 1900-2000; Journalistes - États-Unis - Correspondance; Écrivains américains - 20e siècle - Correspondance; Authors, American -- 20th century -- Correspondence; Journalists -- United States -- Correspondence; USA; Briefsammlung